ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN LAPTOP - Siska Ciswati; Irwan Septayuda (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2023)
The goal to be achieved in this study is to determine the factors that influence consumer behavior on laptop purchasing decisions for Bina Darma University Palembang students. The variables examined in this study are cultural factors, social factors, personal factors, and psychological factors. This type of research uses quantitative methods. Data processing uses SPSS (software package f for t the social science). This study uses hypotheses tests, namely the objective test and the f test as a tool to find out whether cultural factors, social factors, personality factors, and psychological factors influence or do not influence purchasing decisions either partially or simultaneously. Based on the results of the study, t shows that partially cultural factors t counts (2.131) > | t table (1,985)| This shows that there is a significant influence of cultural factors on purchasing decisions and the P value is 0.036 < 0.05. social factors partially t count (2,677) > | t table (1,985)| so this shows that there is a significant influence of social factors on purchasing decisions and the P value is 0.009  < 0.05. personality factor partially t count (2,526) > | t table (1,985)| This shows that the significant influence of personality factors on purchasing decisions and p-value 0.013 < 0.05. Psychological factors partially t count (6.711) > | t table (1,985)| se so that this shows that there is a significant influence of psychological factors on purchasing decisions and the value of the p value is 0.000 < 0.05. Simultaneously, the results of the analysis show that the value of F counts (117,659) > | F table (5,666)| is so that the hypothesis is accepted and the value of the P value is 0.000 < 0.05 is so that cultural, social, personality, and psychological simultaneously have a significant effect on purchasing decisions.